Serum TSH level in hospitalized patients with moderate-to-severe COVID-19 - A. A. Mikhailova; D. I. Lagutina; K. A. Golovatuk; T. L. Karonova; A. T. Andreeva; E. Yu Vasilieva; E. N. Grineva (Медицинский вестник Юга России, 2022)
Objective: to measure the serum TSH level in hospitalized patients with moderate-to-severe COVID-19.Material and methods: this was a retrospective study at Almazov National Medical Research Centre enrolled 133 hospitalized COVID-19 patients without known thyroid disorders. Clinical data, biochemical parameters (TSH, 25(OH)D, C-reactive protein, Lactate dehydrogenase and Ferritin), fi ndings of chest computed tomography (CT) imaging as well as obtained corticosteroids therapy were analyzed.Results: the median TSH level at the 1st-2nd day of hospitalization and at the 9-10th day was 1,15 mIU/L [0, 76; 1, 8] and 1,04 mIU/L [0,7; 1,78] respectively. Th e initial level of TSH <0,4 mIU/L was found in four patients, while by the 9-10th day of hospitalization their number doubled and reached 9 (11,7%). Furthermore, by the 9-10th day of hospitalization the TSH level more than 4,5 mIU/L was detected in four patients (4,2%). Th us, 13 out of 77 patients had the serum TSH level outside the reference range by the 9-10th day of hospitalization.Conclusions: in case of alteration in the serum TSH level it is necessary to take into account the personal history of thyroid disorders. Th e level of thyroid hormones and autoimmune markers as well as thyroid ultrasound results may be useful in clinical interpretation of thyroidal insults during and aft er COVID-19. Th e hypothalamic-pituitary-thyroid axis may also be aff ected by drugs used to treat COVID-19.